Specific effects of SARS-CoV-2 infection on different subtypes of microglia and astrocytes in human brain - JIN Zhongman, WEI Hui (Jichu yixue yu linchuang, 2025)
Objective To investigate the impact of severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) infections on different phenotypes of microglia and astrocytes in the human brain and their role in neurological symptoms resulted from COVID-19 infection. Methods Fourteen human hippocampus-entorhinal cortex (HP-EC) samples were selected including 7 from COVID-19 patients and 7 from control donors. Multiplex immuno-histochemistry was used to detect markers of microglia and astrocytes followed by quantitative evaluation and statistical analysis. Results COVID-19 infection significantly changed density of microglia and astrocytes in HP-EC regions. It led to a decrease in quantity of neuro-protective, neurotoxic, and water-homeostasis-regulating astrocytes, while phagocytic microglia, chemotactic microglia and lipid-transporting astrocytes showed a region-specific density changes. Conclusions COVID-19 infection disrupts immune microenvironment of central nervous system, that may potentially contribute to the pathogenesis of COVID-19-related neurological symptoms as shown by changes of functional states of microglia and astrocytes.